2004
DOI: 10.1021/jp036956o
|View full text |Cite
|
Sign up to set email alerts
|

Combined Raman and Computational Study of a Novel Series of Macrocyclic π-Conjugated Diacetylene-Bridged α-Linked Oligothiophenes

Abstract: We present here a Raman study of a series of macrocyclic molecular materials containing various symmetrically butylated terthienyl or quinquethienyl segments connected through diacetylenic bridges, in the neutral state as solids. Comparison of the Raman features of the macrocycles with those of various linear diacetylenicbridged oligothiophenes of short chain lengths suggests the coexistence in the macrocycles of different molecular conformations. In particular, Raman bands around 2180 cm -1 (due to the diacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…The well‐accepted effective conjugation coordinate (ECC) model developed by Zerbi and co‐workers accounts for the observation of a limited number of overwhelmingly strong Raman scatterings, even for systems with complex chemical structures 35f. 36e This model postulates the existence of a unique collective CC/CC stretching mode strongly involved in the electron–phonon coupling mechanism which characterizes these one‐dimensional π‐conjugated chains 39.…”
Section: Resultsmentioning
confidence: 99%
“…The well‐accepted effective conjugation coordinate (ECC) model developed by Zerbi and co‐workers accounts for the observation of a limited number of overwhelmingly strong Raman scatterings, even for systems with complex chemical structures 35f. 36e This model postulates the existence of a unique collective CC/CC stretching mode strongly involved in the electron–phonon coupling mechanism which characterizes these one‐dimensional π‐conjugated chains 39.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 With the main goal of obtaining relevant structural and molecular information, we have previously studied the Raman spectra of these macrocyclic -conjugated molecular materials, 12 having found that these compounds show unusual features directly related to the degree of -electron delocalization in neutral state. 13 -21 The correlation between the experimental Raman wavenumber and intensity data from one macrocycle to another has allowed, in recent work, the estimation of their effective conjugational properties.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the comparison of the Raman data for the macrocycles and those obtained for a homologous series of openchain oligothiophenes intercalated by a central diacetylene spacer, aided by some Raman vibrational calculations on model systems, has revealed the occurrence of a broadening and/or splitting of the main scatterings upon cyclization, seemingly due to the coexistence of oligothienyl sequences with different conformational arrangements in the same macrocycle. 12 Accordingly, effective -conjugation seems to be scarcely dependent on, infact almost independent of, the molecular conformation of the neutral macrocycle. 12 Nowadays, the completion of this research requires the study of the spectroscopic features of the oxidized forms since many of the applications of these macrocyclic systems are based on the interplay between neutral and stable oxidized species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…www.chemphyschem.org stitution patterns), [16] in most previous articles the systems under study were different homologous series of a-linked oligoheterocycles (i.e. either with linear or cyclic arrangements of the successive p-conjugated rings), but not annulated systems such as acenes or heteroacenes, for which the currently available Raman scattering information is quite scarce in spite of their readily growing relevance in the field of molecular electronics.…”
mentioning
confidence: 99%